Strategi Bauran Pemasaran Industri Tempe Dalam Perspektif Ekonomi Syariah Di Kabupaten Sri Indrapura Provinsi Riau - Nurhadi, Nurhadi; Salim, Agus (Universitas Islam Negeri Alauddin Makassar, 2019)
The fall in the buying and selling numbers in the tempe industry in Kec. Sabak Auh, Kab. Siak Sri Indrapura, Riau. Aims to find out the marketing mix strategy, supporting and inhibiting factors in terms of the Islamic economy of the tempe home industry. The population of 20 people is also the object. Primary data and secondary data obtained by observation, interviews, and questionnaires, then analyzed using descriptive qualitative methods. The result: 1). The marketing mix strategy undertaken by the tempe home industry is still traditional, both in terms of product, location, promotion, and price. 2). Supporting factor is one of the traditional foods, which are popular in the community and sterile from chemicals. The inhibiting factor is the limited raw material for soybeans. 3). Islamic Economics review of the Marketing Mix Strategy undertaken are: 1). Tempeh products are not prohibited. 2). Prices offered are affordable. 3). Place of marketing in strategic locations and easily accessible. 4). Promotion is not yet fully in accordance with the Islamic economic system, because it has not yet maximized to increase sales, it is evident from the aspect of the strategy that it still is. Then the researcher recommends that the results of this study become a consideration for tempe industries in Riau.Keywords: Marketing Mix Strategy, Home Industry, Sharia Economy.Turunnya angka jual beli dalam industri tempe di Kec. Sabak Auh, Kab. Siak Sri Indrapura, Riau. Bertujuan untuk mengetahui strategi bauran pemasaran, faktor pendukung dan penghambat ditinjau dari ekonomi Islam industri rumah tangga tempe. Populasi 20 orang juga sebagai objeknya. Data primer dan data sekunder didapat dengan observasi, wawancara, dan kuesioner, selanjutnya dianalisis dengan metode deskriptif kualitatif. Hasilnya: 1). Strategi bauran pemasaran yang dilakukan industri rumah tangga tempe masih tradisional, baik dari segi produk, tempat, promosi, dan harga. 2). Faktor pendukungnya merupakan salah satu makanan tradisional, yang populer di masyarakat dan seteril dari bahan kimia. Faktor penghambatnya, terbatasnya bahan baku kedelai. 3). Ekonomi Islam meninjau dari Strategi Bauran Pemasaran yang dilakukan adalah: 1). Produk tempe tidak dilarang. 2). Harga ditawarkan terjangkau. 3). Tempat pemasaran di lokasi strategis dan mudah diakses. 4). Promosi belum sepenuhnya sesuai dengan sistem ekonomi syariah, karena belum memaksimalkan untuk meningkatkan penjualan, terbukti dari aspek strategi masih seperti apa adanya. Maka penneliti menganjurkan agar hasil penelitian ini jadi modal pertimbangan para industri tempe di Riau.Kata Kunci: Strategi Bauran Pemasaran, Industri Rumahan, Ekonomi Syariah.